Metode Pengajaran Sejarah Menurut Hamka - HMN, Mas’ud; Husaini, Adian; Saefuddin, Didin (Ta’dibuna: Jurnal Pendidikan Islam, 2014)
This study aims at examining the Hamka’s concept of history education through a descriptive analysis of his life history and his historical works. Through reviewing Hamka life history, it is hope to know how did he make himself to became a historian. While by analyzing Hamka historical works, it is hope to know how did he use the methods of historical thinking in his works. Based on these the Hamka’s concept of history education is then reconstructed whit the emphasis on the goal and method of historical teaching. From the analysis of Hamka life history by framing how he established himself in the field of history, it is concluded that Hamka (1) has a high “interest” in the historical field that grow naturally being raised in an environment that is rich with the art of storytelling (bakaba) and (2) has a high “self efficacy” in independent learning that grow instead of failure in the formal school and then reinforced with a mastery of Islamic Jurisprudence and logic that deliberately was taught by his father in order not to mislead in learning all areas of his interest independently. Especially in the field of history Hamka learn by (3) “observing”, i.e. looking, listening, and asking about the origins of events and important figures in his surrounding environment and in other countries he journeyed, (4) “reading”, i.e. own attempting to gain an understanding of the various readings of history, whether written by the classical historian of Islam, the traditional local historians, and the modern historians including the orientalist and foreign writers, and (5 “writing” , which reproduces the understanding gained from the observations and readings by using his own angle of view, interpretation, and style. Further analysis using the framework of Seixas “historical thinking” on Hamka’s Ayahku: Riwayat Hidup Dr. H. Abdul Karim Amrullah dan Perjuangan Kaum Agama di Sumatra Barat (“My Father: The History of Dr. H. Abdul Karim Amrullah and The Religious Struggle in West Sumatra”), it is clearly visible Hamka’s ability to use historical thinking. In this work Hamka successfully “demonstrate the significance of history”, “use of historical sources“, “analyze continuity and change in history”, “take a historical perspective”, and “presents a moral message of history”. As a self-taught in history, Hamka’s ability intuitively derived from an intelligent reading of the historical works and present his own understanding of learning by way of writing it (writing to learn). What is achieved by this self-taught Hamka, should be achieved by anyone who studied history in formal education. Based on the life history of how Hamka establish himself as a student of history and an analysis of his original work Ayahku, it can be formulated concept Hamka’s history education that useful in developing an ideal history education. From Hamka’s life history, the keywords in his history education is “interest”, “self-efficacy”, “observing”, “reading” and “writing”. While from his historical work analysis the keyword is “think historically.” If all the keywords are formulated through a concise definition, then Hamka’s concept of history education is “fostering interest and self-efficacy of students in historical thinking through the activities of observing, reading, and writing about history.” Keywords: Hamka, Metode Pengajaran, sejarah